Arterial Pulsatility Augments Microcirculatory Perfusion and Maintains the Endothelial Integrity during Extracorporeal Membrane Oxygenation via hsa_circ_0007367 Upregulation in a Canine Model with Cardiac Arrest. (18th February 2022) - Li, Guanhua; Zhu, Shenyu; Zeng, Jianfeng; Yu, Zhexuan; Meng, Fanji; Tang, Zhixian; Zhu, Ping
Abstract : Background . The impairment of microcirculation is associated with the unfavorable outcome for extracorporeal membrane oxygenation (ECMO) patients. Studies revealed that pulsatile modification improves hemodynamics and attenuates inflammation during ECMO support. However, whether flow pattern impacts microcirculation and endothelial integrity is rarely documented. The objective of this work was to explore how pulsatility affects microcirculation during ECMO. Methods . Canine animal models with cardiac arrest were supported by ECMO, with the i-Cor system used to generate nonpulsatile or pulsatile flow. The sublingual microcirculation parameters were examined using the CytoCam microscope system. The expression of hsa_circ_0007367, a circular RNA, was measured during ECMO support. In vitro validation was performed in pulmonary vascular endothelial cells (PMVECs) exposed to pulsatile or nonpulsatile flow, and the expressions of hsa_circ_0007367, endothelial tight junction markers, endothelial adhesive molecules, endothelial nitric oxide synthases (eNOS), and NF- κ B signaling activity were analyzed. Results . The pulsatile modification of ECMO enhanced microcirculatory perfusion, attenuated pulmonary inflammation, and stabilized endothelial integrity in animal models; meanwhile, the expression of hsa_circ_0007367 was significantly upregulated both in animals and PMVECs exposed to pulsatile flow. In particular, upregulation of hsa_circ_0007367 stabilized the expressions of endothelial tight junction markers zonula occludens- (ZO-) 1 and occludin, followed by modulating the endothelial nitric oxide synthases (eNOS) activity and inhibiting the NF- κ B signaling pathway. Conclusion . The modification of pulsatility contributes to microcirculatory perfusion and endothelial integrity during ECMO. The expression of hsa_circ_0007367 plays a pivotal role in this protective mechanism.